Diversity in action : managing diverse talent in a global economy - Latukha, Marina (Emerald Publishing Limited, 2022)
Diversity in Action: Managing Diverse Talent in a Global Economy examines one of the most important and topical issue related to diversity management, namely implementing effective strategies for managing diverse talent groups. Highlighting both theoretical issues regarding diversity management and their practical implications, Marina Latukha's wide ranging collection investigates how different management practices focusing on diverse talent groups are realised in order to provide systematic assessments on existing diversity challenges. Diversity in Action uniquely features diversity within diversity as the main topic within its analysis. Content covers different types of employees in its focus of diversity management practices in global economies. Groups explored in relation to human resource and talent management practices include but not limited to management of different generations and migrants and diaspora' representatives employed in modern organizations. There is also discussion of gender-focused initiatives to present the dialog about female talent management and the way it influences organizational results. Diversity in Action highlights the latest development in relation to strategies and practices on diversity management, providing specific examples of how different talent diverse groups should be involved in organizational business processes and effectively managed.